A community perceptions based on cost-benefit analysis approach to developing a tourism route : a case study of Umjindi Local Municipality - Sekole, Makhupu Queen (My University, 2016)
The purpose of this study was to determine the community perceptions based on cost–benefit analysis approach to developing a tourism route. The Ehlanzeni District Municipality in the Mpumalanga Province is proposing the development of a new community-based tourism route in the Umjindi Local Municipality. The route will start from the R40 road gateway to Umjindi Local Municipality, it then stretches to Umjindi township, ending in Barberton town. The aim of a tourism route is brings together a variety of activities and attractions under a theme, and it develops opportunities of products and services. The literature review in the study is drawn from host communities’ perception on tourism development, South African and international perspective on cost–benefit analysis of tourism development. Routes are considered important because they promote local economic development. The impact of tourism development in a local society is demonstrated throughout this study. Through an analysis of the qualitative and quantitative data collected, it was found that community perceived the cost is less than what they will actually benefit from the development of the proposed tourism route. The community perceives that the costbenefit of the development of a tourism route is associated with issues of the economy, social, cultural and environment.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Cost–benefit analysis; Community-based tourism route; Tourism; Community development; Cost effectiveness; Economic development projects -- Cost effectiveness; Tourism -- South Africa -- Mpumalanga; Community development -- South Africa -- Mpumalanga